EDUCATION AND TRAINING Training educational supervisors to support physician trainees returning to practice. Issue 2 (2020) - Hallewell, Rosalyn; Bryant, Catherine; Deaner, Andrew; Ruggles, Ruth; Birns, Jonathan
No abstract available